Early maternal deprivation affects dentate gyrus structure and emotional learning in adult female rats - Oomen, Charlotte A. (Springer-Verlag, 2010)
RATIONALE: Stress elicits functional and structural changes in the hippocampus. Early life stress is one of the major risk factors for stress-related pathologies like depression. Patients suffering from depression show a reduced hippocampal volume, and in women, this occurs more often when depression is preceded by childhood trauma. However, the underlying mechanisms that account for a reduced hippocampal volume are unknown. OBJECTIVE: We examined the effects of maternal absence on structure and function of the hippocampus in female offspring. METHODS: We studied whether 24 h of maternal deprivation (MD) on postnatal day 3 altered adult neurogenesis, individual neuronal morphology and dentate gyrus (DG) structure in young adult female rats. In addition, functional alterations were addressed by studying synaptic plasticity in vitro, and spatial as well as emotional learning was tested. RESULTS: Adult females that were subjected to MD revealed significant reductions in DG granule cell number and density. In addition, DG neurons were altered in their dendritic arrangement. No effects on the rate of adult neurogenesis were found. Furthermore, MD did not alter synaptic plasticity in vitro, neither under normal nor high-stress conditions. In addition, spatial learning and contextual fear conditioning were comparable between control and MD animals. However, MD animals showed an improved amygdala-dependent fear memory. CONCLUSION: Although early life stress exposure did not impair hippocampus-dependent functioning in female offspring, it irreversibly affected DG structure by reducing cell numbers. This may be relevant for the reduced hippocampal volume observed in depression and the increased vulnerability of women to develop depression.